Knowledge and Awareness of Rural School Teachers Regarding Risk Factors of Common Non-communicable Diseases (Journal of Preventive and Social Medicine, 2025)
Background: Non-communicable diseases (NCDs) are currently a huge burden on the health situation. Noncommunicable diseases kill 41 people each year, equivalent to 74% of all deaths globally. In Bangladesh, 67% of all deaths are caused by NCDs. Bangladesh’s healthcare spending from 2000 to 2022 was $46. This study aimed to assess the knowledge and awareness level of rural school teachers about common risk factors of noncommunicable diseases. Methods: A descriptive type of cross-sectional study was conducted among rural school teachers of Shibganj Upazila, Bogura. A total of 334 rural school teachers were selected by purposive sampling technique. Data were collected using pre-tested semi-structured questionnaires and SPSS version 25 was used for data analysis. Frequency and percentage were used to describe the variables. Inferential statistics included Chi square test / Fisher’s exact test to find out any significant association between two qualitative variables. Results: The result of this study showed most of the respondents 149(44.6%) were 31-42 years old with the mean age of respondents being 42.26 years which ranged from 21-58 years. Female (51.5%) outnumbered male (48.5%). Most of the respondents 91.9%(n=334) had good knowledge about common risk factors of NCDs and among those who had good knowledge majority of them, 87.9% were aware. The association between the level of knowledge and the level of awareness of the respondents were found statistically not significant (p>0.05). Conclusion: Since the majority of these risk factors are modifiable through behavioral changes, proper knowledge and awareness about common risk factors of NCDs in rural school teachers lead to reduce the burden of NCDs globally and help to prevent the development of NCDs from an early age of life of their students and rural community.JOPSOM 2024; 43(1): 33-40